(untitled) (Journal of Dhaka National Medical College & Hospital, 2024)
Objective: The aim of the present study was to compare the findings of CXR and echocardiography in determination of the heart size. Methods: A cross sectional study was conducted from January 2019 to June 2019 among 100 patients attending at Cardiology Department, Cumilla Medical College Hospital, Cumilla after obtaining requisite consent from the patients. Data were collected through the assessment of patients in the Cardiology Department. The collected data were entered into the computer and analyzed by using SPSS (version 20.1) to compare the findings of CXR and echocardiography in determination of the heart size. The study was approved by the institutional ethical committee. Results: In 100 patients’s, majority 68% was between 30-50 years and 32% was between 50-90years. Among 100 patients, 64% was female and 36% was male. 36% patients were suffering from hypertension while 12% patients were suffering from Diabetes mellitus and 2% patients suffering from Dyslipidemia. Edema was present in 14% patients. 46% patients had cardiomegaly according to the findings of Chest x-ray. 26% patients Right Ventricular end diastolic dimension in Echo was 25-45mm which was considered as a cardiomegaly. 36% patients Left Ventricular end diastolic dimension in Echo was 55-60mm which was considered as a cardiomegaly. 12% patient’s left ventricular ejection fraction was 37-50%. Conclusion: Echocardiography is superior to chest radiography for providing a better assessment of cardiomegaly. J. Dhaka National Med. Coll. Hos. 2024; 30 (01): 35-37